Building a certifiable source device-independent quantum random number generator - Qiu, Kaiwei (Nanyang Technological University, 2023)
Random numbers play an essential role in various fields, especially cryptography. This is because of the randomness and unpredictability that they provide. Due to the intrinsic randomness in quantum theory, the Quantum Random Number Generator (QRNG) is an excellent device to fulfil this requirement. However, QRNG is vulnerable to quantum attacks by eavesdroppers, which compromises the quality of the generated random numbers. Such attack includes tampering with the QRNG light source. With this consideration in mind, following the work of Drahi et al. on Source Device-Independent (SDI) QRNG, we construct a cost-effective SDI-QRNG that uses off-the-shelves and highly customizable components that could certify random numbers from an untrusted light source. In addition, after reviewing the SDI protocol, a generalised SDI protocol for unbalanced homodyne detection was proposed. Under this protocol, the randomness generation manages to produce certified raw random bits at a rate of 233kb/s from untrusted light. On the other hand, in the proof-of-concept of real-time random number extraction, a string of certified hashed random numbers is extracted at a rate of 1.20kb/s that is composably secure with failure probability ε = 5 × 10−10. Composable security is a crucial feature for any QRNG protocol, as it verifies that the random numbers extracted are quantum secure for use. Lastly, the SDI-QRNG demonstrated its security against quantum attacks via light injection by certifying fewer random numbers.